Effect of Fly Ash Addition on Linoleic Acid Content of Seeds of H. annuus - Dwivedi, Jaya; Khan, S.A. (Asian Journal of Chemistry, 2016)
Nutritional value of seeds of H. annuus (sunflower) depends on contents of PUFA and amino acids. PUFA content of seed is affected by soil pH nutrient availability. It was found to increase on fly ash addition as the latter has good nutrient content and high pH.